Evaluation of Beauveria bassiana pathogenicity in the coffee berry borer using the leaf spraying method - POSADA-F., FRANCISCO J.; OSORIO-V., EDUARDO; VELÁSQUEZ-S., ELENA T. (Revista Colombiana de Entomología, 2002)
The results of Beauveria bassiana (Balsamo) Vuill. pathogenicity test on the coffee berry borer (CBB) through the application the spores in droplets are presented. Adults of CBB were exposed for one minute on coffee leaves treated with four droplets with coverage/cm2 (3, 9, 27, 81). In each droplet 3, 9, 27, and 81 spores, respectively were estimated to be delivered. The spores were formulated in two experimental oil-based formulations: Kerosene + Carrier (60:40) and Carrier + Water (50:50). The mortality was higher for K + C (85.5 ± 17.0%) followed by C + W (70 ± 25.8%) when the spores were sprayed using 81 spores/ droplet and a coverage of 81 droplets/cm2. The mortality tendency showed no direct relationship between the number of spores and the droplets. The mortality response was more variable with K + C than with C + W. The CL50 and CL80 were estimated in 15 and 75 spores/droplets when 81 droplets/ cm 2 were applied loaded with 3, 9, 27 and 81 spores/ droplets, on average. The data suggest that the formulation can affect the CBB behavior and therefore the picking up and encountering of spores from a treated surface. The lethal concentrations, 50 and 80 were calculated with the software Probit and were estimated at between 15 and 70 spores.